Scoping Review: The Effect of Murottal Al-Qur'an Therapy on the Anxiety Levels of Pregnant Women Pre-Caesarean Operation - Rahayu, Widya; Kartini, Farida (Poltekkes Kemenkes Palu, 2024)
Pregnant women may experience anxiety after a cesarean section with various complications. Intervention to reduce anxiety levels non-pharmacologically is through Murottal Al-Qur'an therapy. The aim of the research was to analyze the effect of Murottal Al-Qur'an therapy on the anxiety level of pregnant women before caesarean section. This research method uses a descriptive design with a scoping review approach. Article searches used four journal databases, PubMed, ScienceDirect, EBSCO, and Google Scholar. Articles that met the inclusion criteria, including a publication range from 2013 to 2022 in English and Indonesian and free access to the full-text PDF, were evaluated before selection. The research results show that from all the articles studied, Al-Qur'an Murottal therapy can reduce pre-operative anxiety in pregnant women. Listening to the Murottal reading of the Qur'an via audio is an alternative that can be a calming reminder and remind yourself. Advice for pregnant women who will undergo surgery not to think about bad things that can make them feel anxious because the effect of Al-Qur'an murottal intervention can reduce anxiety in pregnant women before Caesarean surgery.